Novel Somatic UBA1 Variant in a Patient With VEXAS Syndrome - Stiburkova, Blanka; Pavelcova, Katerina; Belickova, Monika; Magaziner, Samuel J; Collins, Jason C; Werner, Achim; Beck, David B; Balajkova, Veronika; Salek, Cyril; Vostrý, Martin; Mann, Herman; Vencovsky, Jiri (Arthritis & rheumatology, 2023)
OBJECTIVE: Somatic mutations in UBA1 have recently been causally linked to a severe adult-onset inflammatory condition referred to as VEXAS (vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic) syndrome. Ubiquitin-activating enzyme E1 (UBA-1) is of fundamental importance to the modulation of ubiquitin homeostasis and to the majority of downstream ubiquitylation-dependent cellular processes. Direct sequencing analysis of exon 3 containing the prevalent variants p.Met41Leu, p.Met41Val, and/or p.Met41Thr is usually used to confirm the disease-associated mutations. METHODS: We studied the clinical, biochemical, and molecular genetic characteristics of a 59-year-old man with a 2-year history of arthritis, fever, night sweats, nonspecific skin rash, lymphadenopathy, and myelodysplastic syndrome with multilineage dysplasia. RESULTS: The mutational analysis revealed a previously undescribed sequence variant c.1430G>C in exon 14 (p.Gly477Ala) in the gene UBA1. In vitro enzymatic analyses showed that p.Gly477Ala led to both decreased E1 ubiquitin thioester formation and E2 enzyme charging. CONCLUSION: We report a case of a patient of European ancestry with clinical manifestations of VEXAS syndrome associated with a newly identified dysfunctional UBA-1 enzyme variant. Due to the patient's insufficient response to various immunosuppressive treatments, allogeneic hematopoietic stem cell transplantation was performed, which resulted in significant improvement of clinical and laboratory manifestations of the disease.
Keywords: mutace; dospělí; ubikvitin aktivující enzymy; Myelodysplastic Syndromes; Patients; lidé středního věku; lidé; mužské pohlaví; myelodysplastické syndromy; ubikvitiny; Male; Ubiquitin-Activating Enzymes; Ubiquitins; Middle Aged; Mutation; Adult; pacienti; Humans